Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1056/nejmoa070594
|View full text |Cite|
|
Sign up to set email alerts
|

Lenalidomide plus Dexamethasone for Relapsed or Refractory Multiple Myeloma

Abstract: Lenalidomide plus dexamethasone is more effective than high-dose dexamethasone alone in relapsed or refractory multiple myeloma. (ClinicalTrials.gov number, NCT00424047 [ClinicalTrials.gov].).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

52
1,054
8
22

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,329 publications
(1,136 citation statements)
references
References 12 publications
52
1,054
8
22
Order By: Relevance
“…Furthermore, in accordance with published reports (van Rhee et al , 2014), patients who had undergone SCT were more likely to achieve CR than those who had not. Moreover, efficacy outcomes were broadly similar to those seen in clinical trials (Singhal et al , 1999; Richardson et al , 2005; Dimopoulos et al , 2007; Weber et al , 2007; San Miguel et al , 2013). Achievement of CR or VGPR was also associated with a greater likelihood of receiving a further line of treatment.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Furthermore, in accordance with published reports (van Rhee et al , 2014), patients who had undergone SCT were more likely to achieve CR than those who had not. Moreover, efficacy outcomes were broadly similar to those seen in clinical trials (Singhal et al , 1999; Richardson et al , 2005; Dimopoulos et al , 2007; Weber et al , 2007; San Miguel et al , 2013). Achievement of CR or VGPR was also associated with a greater likelihood of receiving a further line of treatment.…”
Section: Discussionsupporting
confidence: 70%
“…Given the availability of agents that are effective in relapsed and refractory MM (Singhal et al , 1999; Richardson et al , 2005; Dimopoulos et al , 2007; Weber et al , 2007; Offidani et al , 2013; San Miguel et al , 2013; San‐Miguel et al , 2014; Stewart et al , 2015), it is perhaps surprising that relatively few patients receive multiple lines of therapy. About a quarter of patients completed fourth‐line treatment as planned, and 38% of patients ended fourth‐line treatment in remission, suggesting that patients do benefit from receiving treatment at this later stage; however, very few reach fifth‐line treatment (1%).…”
Section: Discussionmentioning
confidence: 99%
“…Our observations confirm the neutropenia rates reported in the European/Australian [8] and North American [9] phase 3 trials of lenalidomide and dexamethasone, as well as a recent phase 3 study [6]. Neutropenic toxicity was associated with clinical consequences: patients with grade 3/4 neutropenia had more lenalidomide exposure reductions, G-CSF use, and unplanned hospitalization relative to those without neutropenia.…”
Section: Discussionsupporting
confidence: 87%
“…Statistical analysis. Assuming an incidence of grade 3/4 neutropenia of 40% based on the literature [8,9,19], a sample size of 200 patients (allowing a 6% dropout rate) would enable 95% confidence intervals to be calculated to within a precision of 67%. As prespecified, only patients who met the eligibility criteria and who started 1 cycle of lenalidomide plus dexamethasone therapy were included in the primary analysis set.…”
mentioning
confidence: 99%
“…Approximately one-third of patients with relapsed refractory myeloma respond to bortezomib when used as a single agent [36]. Two large Phase III trials have shown superior TTP and OS with lenalidomide (25 mg oral days 1-21 every 28 days) plus dexamethasone compared with placebo plus dexamethasone in relapsed multiple myeloma [106,107]. Bortezomib and the immunomodulatory drugs (thalidomide or lenalidomide) can be combined effectively with each other and with other chemotherapy drugs such as cyclophosphamide and melphalan to produce highly active combination regimens.…”
Section: Treatment Of Relapsed Multiple Myelomamentioning
confidence: 99%